2014
DOI: 10.1590/s2179-975x2014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of aerobic decomposition in the leaching phase of allochthonous plant detritus

Abstract: AIMS: This study aimed to evaluate, through an experiment with short sampling intervals, (1) the effects of detritus quality on dissolved oxygen (DO) consumption, on dissolved inorganic carbon (DIC) formation and on the stoichiometric ratio between the DO consumed and mineralized carbon (O/C ratio) during leaching of plant detritus in the early decomposition; (2) the temporal variation of the variables mentioned above according to changes in the quality of each detritus over time. METHODS: The detritus of leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As indicated by this work, as well as others (Grünheid et al, 2005; Fonseca et al, 2014; Liu et al, 2021), portions of recharged terrestrial DOM can be oxidized in hours to weeks. This oxidation limits concentrations of DOC in regions of aquifers far from locations of point recharge, for example where springs reverse flow or proximal to sinking streams.…”
Section: Discussionsupporting
confidence: 81%
“…As indicated by this work, as well as others (Grünheid et al, 2005; Fonseca et al, 2014; Liu et al, 2021), portions of recharged terrestrial DOM can be oxidized in hours to weeks. This oxidation limits concentrations of DOC in regions of aquifers far from locations of point recharge, for example where springs reverse flow or proximal to sinking streams.…”
Section: Discussionsupporting
confidence: 81%
“…e TBI Applied and Environmental Soil Science calculations are also based on green tea leaves going through both phases of biphasic decomposition and reaching a plateau after 90 days incubation, whereas rooibos tea should still be decomposing. Litter decomposition goes through two phases with a fast initial loss of soluble components through leaching into the soil, followed by a more gradual mass loss due to microbial decomposition and mineralization of cellulose and other compounds [21,22]. e mass of the green tea decline was biphasic with rapid decline to 14 d, and loss of soluble tannins, followed by a slower rate to 91 d, while the mass of rooibos tea declined at a slow rate over the whole incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the leaching of labile materials is preponderant in the initial stage of decomposition (Baxter ; Aerts & de Caluwe ; Fonseca et al . ), being responsible for the intense loss in detritus mass (Bianchini & Cunha‐Santino ; Fonseca et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), being responsible for the intense loss in detritus mass (Bianchini & Cunha‐Santino ; Fonseca et al . ). In the initial stage, the hydrostatic pressure could likely force leaching because of the physical action of compressing the detritus, although no significant influence was observed during this stage.…”
Section: Discussionmentioning
confidence: 99%